(untitled) (Research, Society and Development, 2021)
Quail skin is not taken into account because it is very small and apparently fragile, but with tanning it can increase its resistance and add good value when used in certain products. Also, after tanning, as it is a fine leather with a certain elasticity, it can be used for detail applications in garments, shoes, bags, fine jewelry or even various accessories. This study aimed to evaluate the skin resistance of posture-type quail (Coturnix coturnix japonica) after a tanning process. The hides were submitted to soaking, lime, deliming, purging, degreasing, piquel, tanning, neutralization, retanning and dyeing, grease, fixation, drying and softening steps. After the entire tanning process, the specimens were removed for strength tests (progressive tearing, traction and elongation). The quail hide had a thickness ranging from 0.38 to 0.42 mm, whose progressive tear strength was 4.11 N/mm, with a tensile determination of 2.56 N/mm2 and elongation of 39.1% . Quail hides, after tanning with chromium salts, presented a thin thickness and very low resistance to progressive tearing and traction, as well as low elasticity. Therefore, a fragile leather for application in clothing, despite the possibility of use in small accessories or some types of artifacts.